EVOLUTION OF URBAN PLANNING IN PERU 1946 - 2021: FROM NORMATIVE URBAN PLANNING TO SUSTAINABLE URBAN DEVELOPMENT PLANNING - Castillo-García, Rodolfo Francisco (2021)
This article constitutes an approach to the study of the evolution of urban planning in Peru in the period 1946-2021, based on the legal framework and the institutional framework in the country, and based also on the contemporary urban planning approaches that have influenced it. In this virtue, an identification of periods in the evolution of urban planning in Peru is proposed and developed: 1946-1968, 1969-1980, 1981-1991, 1992-2005 and 2006-2021, which could mean an evolution since the “normative urban planning” of the first decades of the 20th century, to the “planning of sustainable urban development” in the second decade of the 21st century. Keywords: urban planning - normative urban planning - sustainable urban development planning